Postharvest decay development on guava stored under several controlled atmosphere conditions - Teixeira, G. H A; Durigan, J. F. [UNESP]; Santos, L. O. [UNESP]; Ogassavara, F. O. [UNESP] (My University, 2012)
The control of post-harvest fungal decay on guava (Psidium guajava L. 'Pedro Sato') stored under low oxygen controlled atmosphere (5 kPa) was compared with increasing concentrations of carbon dioxide in the atmospheres. The combination of high concentrations of carbon dioxide (1, 5, 10, 15 and 20 kPa) with low oxygen (5 kPa) did not result in additional decay control. The low oxygen level (5 kPa) was the main factor for controlling post-harvest fungal development which resulted in a very low percentage of fruits with symptoms of anthracnose and stylar end rot throughout cold storage, regardless of the CO2 concentration. After transfer to ambient conditions, only the atmospheres with 5 kPa O2 (control), 5 kPa O2 + 1 kPa CO2 and 5 kPa O2 + 5 kPa CO2 resulted in reduced incidence of stylar end rot (P<0.05). There was not a significant interaction among CA combinations and storage duration on the percentage and number of typical anthracnose lesions.
Keywords: Carbon dioxide; Colletotrichum gloeosporioides; Oxygen; Physical treatment; Glomerella cingulata; Psidium; Psidium guajava